PERAN TRADISI GOTONG ROYONG DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI MASYARAKAT DI DESA KARANGPUCUNG DALAM PERSPEKTIF EKONOMI ISLAM - Sudrajat, Bayu; Yasin, Roqi; Wigiyanti, Wigi; Marlvasha, Leira Salwa (AT-THARIQ: Jurnal Studi Islam dan Budaya, 2024)
This research examines the role of the mutual cooperation tradition in improving the economic welfare of the Islamic community in Karangpucung Village from an Islamic economic perspective. The research introduction explains that mutual cooperation is a long-standing tradition in village communities, with significant potential to influence economic prosperity through social solidarity and collaboration. The research method used is a qualitative approach using interview techniques and in-depth observation to obtain data about mutual cooperation practices and their impact on the community's economy. The research results show that mutual cooperation significantly contributes to improving economic prosperity by strengthening social networks, increasing productivity, and facilitating a more equitable distribution of resources, which is in line with Islamic economic principles such as social justice and wealth distribution.Keywords: Mutual Cooperation, Welfare, Islamic Economics.